DEFORMATIONAL BEHAVIOR OF FIBER REINFORCED CEMENT BASED MATERIALS UNDER REPEATED LOADING - Zede (Zede Journal of Ethiopian Engineers and Architects, 2024)
Bond degradation of the constitutematerials of the structure causes an increase in residual deflection and total surface crack width which reduces overall performance of structures. Advanced construction materials such as ultra-high strength fiber-reinforced concrete,commonly known as engineered cementitious composite (ECC) and fiber reinforced strain-hardening cement-based composites (SHCC)are designed to offer superior mechanical properties with multiple fine cracks and deformability than conventional concrete materials because of the bridging effect of embedded fibers. In general, both ECC and SHCC can be suitable for applications involving repeated loadings. However, the performance depends on magnitude, type of loads, etc. In this study, deformational behavior of fiber reinforced cement-based materials, ECC and SHCC, under repeated loading (low cycle fatigue) is investigated. Test results showed that, ECC is bendable, the deformation can be easily detected and has high impact resistance. On the other hand, SHCC has the potential for multiple cracking and strain-hardening behavior. ECC and SHCC can thus be used for strengthening and retrofitting of structural lements in addition to their benefits for new construction works.